2006
DOI: 10.1161/01.str.0000206458.58142.f3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Metabolic Syndrome and General Obesity on the Risk of Ischemic Stroke

Abstract: Background and Purpose-In 2005, the National Cholesterol Education Program Adult Treatment Panel III (NCEP-ATP III) guideline lowered the fasting glucose cut point used to define metabolic syndrome (MS). This study investigated the influence of MS on ischemic stroke (IS) risk using both the original and revised definitions. In addition, because abdominal obesity is the measure of obesity used in the guideline to define MS, we also investigated whether general obesity ( Adding GOB to the existing MS definition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
87
0
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 128 publications
(101 citation statements)
references
References 18 publications
8
87
0
5
Order By: Relevance
“…A previous validation study comparing ICD coding and hospital record review in Taiwan has showed that sensitivity and specificity for major cardiovascular events such as stroke were 100% and 95%, respectively, suggesting the high positive predictive value for a major cardiovascular event in which hospitalization is needed. (39) Another study also demonstrated a high positive predictive value up to 95% for acute myocardial infarction diagnosis after comparing ICD coding from Medicare claims and a diagnosis based on structured hospital record review, (40) further supporting the accuracy of AMI diagnosis in our study. Third, although hip fracture patients had higher mortality in the current study, we did not know the exact cause of death for each enrollment, especially those deaths that occurred outside of hospitals.…”
Section: Discussionsupporting
confidence: 80%
“…A previous validation study comparing ICD coding and hospital record review in Taiwan has showed that sensitivity and specificity for major cardiovascular events such as stroke were 100% and 95%, respectively, suggesting the high positive predictive value for a major cardiovascular event in which hospitalization is needed. (39) Another study also demonstrated a high positive predictive value up to 95% for acute myocardial infarction diagnosis after comparing ICD coding from Medicare claims and a diagnosis based on structured hospital record review, (40) further supporting the accuracy of AMI diagnosis in our study. Third, although hip fracture patients had higher mortality in the current study, we did not know the exact cause of death for each enrollment, especially those deaths that occurred outside of hospitals.…”
Section: Discussionsupporting
confidence: 80%
“…Obesity and overweight have been widely studied because they entail serious medical problems such as non-alcoholic fatty liver disease, cardiovascular disease, stroke, and endothelial dysfunction (Lteif et al 2005, Chen et al 2006, Bell 2009, Khoshdel et al 2012. Maternal obesity and overweight affect fetal growth and development.…”
Section: Introductionmentioning
confidence: 99%
“…Although metabolic syndrome has been recognized as a risk factor for atherosclerotic diseases such as coronary heart disease (2,3) and ischemic stroke (4)(5)(6)(7)(8), genetic risk for ischemic stroke in individuals with metabolic syndrome has remained uncharacterized. Given that stroke is the leading cause of severe disability and the third leading cause of death, after heart disease and cancer, in western countries and Japan (9), the identification of biomarkers for stroke risk is important both for risk prediction and for intervention to avert future events.…”
Section: Introductionmentioning
confidence: 99%